Induction of Microspore Embryogenesis of Eggplant (Solanum melongena L.) ‘Gelatik’ - Devi Bunga Pagalla; Ari Indrianto; Maryani Maryani; Endang Semiarti (Journal of Tropical Biodiversity and Biotechnology, 2020)
The haploid or double haploid plant of eggplants could be produced from microspore culture (embryogenesis of microspores). In the breeding programs, microspore can be developed into an embryo directly after exposure to stress treatment during cultured. Stress (temperature and starvation medium) is an important factor in the induction of embryogenesis microspore. This study aims to induced embryogenic microspores from eggplant CV. Gelatik. The stage late-uninucleate microspore (Vacuolate Microspore/VM) and early binucleate (Young Bicellular Pollen/YBP) are the suitable stages to induce multinucleate structure. There are 3 methods used in this research; 1) Determination of the stage development of microspore based on flower buds length and anther length. 2) Induction of embryogenic microspore on the pre-treatment and starvation medium. 3) After giving pre-treatment for 4 days, micropores were transferred to culture medium A2 at 28oC in dark conditions to induce the multicellular structures. This study reported that 50-68.51% of the VM+YBP stage obtained in the range of flower bud lengths of 10-17 mm, and 5.0-6.9 mm, the range of anther length containing VM+YBP of 50-77.48%. The pre-treatment heat shock at 33oC in the medium B for 2 days,  produced embryogenic microspores with a high percentage, that is about 50.19%, while microspores at 25oC and 4oC respectively 46.17% and 49.28%. Pre-treatment for 4 days at 4 oC, 25 oC,  and 33oC with the percentage of embryogenic microspores apiece 32.87%, 27.45%, and 37.34%. The multicellular (starlike) structure begins forming on the fifth day of incubation in culture medium (A2) after pre-treatment in B medium at 33oC.